Cooperation and leadership in a segregated community: Evidence from a lab-in-the-field experiment in a South African township - Daniela Grieco; Michela Braga; Francesco Bripi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The paper presents the results of a lab-in-the-field experiment in three South African townships located in the suburbs of Cape Town. The experimental design consists of a set of decisions on how the members of a naturally occurring group allocate an endowment to a private or to a public account. In our treatments, we first manipulate the degree of participation of group members in the choice of the public good, from involvement of the group leader only, to collective discussion and to private voting. Additionally, we explore the effectiveness of monetary incentives (collective versus individual) set in order to promote participation. The results show that leader guidance and participatory incentives significantly raise cooperation and hold after controlling for a wide set of individual and group characteristics.
Keywords: C93; D63; D71; H41; O12; 330; lab-in-the-field experiment; segregation; cooperation; leadership; participation; township